ESTUDIOS SOBRE LOS ERITROBLASTOS I CARACTERES DE LOS ERITROBLASTOS DE LA MEDULA OSEA DEL CONEJO - GONZALEZ GUZMAN, IGNACIO; GALINDO MARTINEZ, G; CRUZ VARGAS, J DE LA (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1949)
The concepts of various authors regarding the mechanism of production of the para-erythroblasts in fetal erythroblastosis are discussed and rejected To elucidate this problem a slight hypoglobinemia was produced in rabbits by bleeding Intraperit injn
BOL MEN BAN REF JAL
Keywords: ESTUDIOS, ERITROBLASTOS, CARACTERES, MEDULA OSEA, CONEJO; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; COMPORTAMIENTO ANIMAL